Assessment of wind and solar energy potentials in Malaysia - Belhamadia A.; Mansor M.; Younis M.A. (IEEE Computer Society, 2023)
Renewable energy sources This paper presents a comparison between five different cities in term of wind and solar energy potentials. It first describes the Weibull distribution functions and then analyzes the data collected from the Malaysian Meteorological Department. It then shows the average wind speed and the operation probability of a wind turbine with a cut in speed of 2.5m/s over the five chosen cities. Power density at the wind turbine's hub height is calculated with the annual operating hours of the turbine. Second, this paper compares the power output of a certain PV module in these five different cities. The implication of this study is that it gives an overall review on the wind and solar energy potentials in Malaysia and its results are significant for feasibility and optimization studies. The data obtained from the Malaysian Meteorological Department are on a daily basis from 2011 to 2012. 2013 IEEE.